Gender budgeting in the post-pandemic period: an analysis in the context of health and safety of women in India - Barman, Kanksha; Gupta, Indrani (Frontiers in Public Health, 2025)
Indian women suffered disproportionately due to the COVID-19 pandemic, with the loss of livelihoods, a steep increase in care work due to lockdowns, and the presence of a deeply patriarchal society that expects women to shoulder the brunt of unpaid domestic labor, as well as increasing incidents of violence. This study analyzes whether the post-COVID gender budgets in India adequately responded to the needs of women highlighted by the pandemic. We examine the six most recent gender budgets of the Government of India to analyze whether appropriate changes were introduced, keeping in mind the impact of COVID-19 on women. We find minimal changes in allocations, with only a slight increase in total allocations over the last two budgets, despite alterations within budget allocations. We find that the bulk of the allocations in the gender budget are limited to a few key ministries, with the main focus of the gender budget having been on rural development, housing, education, livelihoods, health, and nutrition. We also analyzed health, employment, and empowerment indicators for women to examine whether there have been improvements in these areas, and found that while some of the basic health indicators have improved, labor force participation rates and political empowerment of women have declined. We conclude that to actually make a difference to the status of women, one has to go beyond mere participation statistics and look at the needs, concerns, and challenges faced by women. Policymakers need to work with communities and grassroots organizations that work closely with and represent women. A top-down approach with routine budget allocations under the gender budget umbrella might, in fact, do a disservice to the cause by bringing in complacency, which India can ill afford.